THE ANALYSIS OF STUDENTS’ PERCEPTION ON THE USE OF GOOGLE CLASSROOM IN SUBMITTING THEIR ASSIGNMENT IN TRANSLATION SUBJECT ON THE THIRD YEAR STUDENTS OF ENGLISH DEPARTMENT OF FKIP UMMY SOLOK - Tia Mariadi; Fitri Handayani; Marsika Sepyanda (Universitas Mahaputra Muhammad Yamin, 2019)
This research was conducted at the third year students of English Department Universitas Mahaputra Muhammad Yamin Kota Solok 2017/2018 academic year. This research was aimed to know the students’ perception on the use of Google Classroom in submitting their assignments in Translation Subject. The background of the research based on the problems that raised by the students who had problems in submitting their Translation Subject assignments. The lecturer copes the problems by using Google Classroom as a media for submitting students’ assignments. This research was conducted by using descriptive method. The subject of the research was the third year students of English Department of Universitas Mahaputra Muhammad Yamin 2017/2018 academic year. In collecting the data, researcher used questionnaire.The findings of this research showed that the students’ perception on the use of Google Classroom in submitting their assignments in Translation Subject was in “good” level. It means that, the students’ perception on the use of Google Classroom in submitting their Translation Subject assignments of universitas mahaputra Muhammad yamin was good. It can be seen by the students’ positive response in responding the questionnaire statements about Google Classroom in submitting their assignments in Translation Subject. This research gives suggestion to the lecturer to use Google Classroom as a media in submitting assignments. For the students, it expected to be more interested and active in using Google Classroom.